Building a Project Portfolio in a Social Enterprise. Analysis and Implementation of Project Selection Methods - Andreasik, Mariusz (Regional Barometer. Analyses & Prognoses, 2013)
The research which is described in the article aimed to help the social enterprise — SIFE Salford in creating a portfolio of projects. The paper focuses on a selection method that the organization may use while choosing among the projects submitted by external enterprises. This process is very complex and it is often difficult to make sound decisions, therefore introducing the methods and the process is essential and beneficial for every organization. The author examines two methods: the scoring and Analytical Hierarchy Process (AHP). An analysis of those methods is made to decide which one is more suitable and useful for the organization under study. Furthermore, the methods are analyzed and studied as to how they can be applied and used in social enterprises. The survey and interviews with experts from the field aim to create guidelines for SIFE Salford, how to use the techniques and benefit from them. Consequently, the President and Directors of the enterprise are trained during the interview process to use the studied methods so that they can be easily implemented in the upcoming academic year. This condenses the aim of the research, which is to experiment among the selection methods that could be a practical tool for a social enterprise to ease the process of selection. It also introduces the concept of project portfolio management within this sector.